Sustained Systemic Antioxidative Effects of Intermittent Theta Burst Stimulation beyond Neurodegeneration: Implications in Therapy in 6-Hydroxydopamine Model of Parkinson's Disease - Milica Zeljkovic Jovanovic; Jelena Stanojevic; Ivana Stevanovic; Milica Ninkovic; Nadezda Nedeljkovic; Milorad Dragic (MDPI AG, 2024)
Parkinson's disease (PD) is manifested by the progressive loss of dopaminergic neurons in the substantia nigra pars compacta (SNpc) and caudoputamen (Cp), leading to the development of motor and non-motor symptoms. The contribution of oxidative stress to the development and progression of PD is increasingly recognized. Experimental models show that strengthening antioxidant defenses and reducing pro-oxidant status may have beneficial effects on disease progression. In this study, the neuroprotective potential of intermittent theta burst stimulation (iTBS) is investigated in a 6-hydroxydopamine (6-OHDA)-induced PD model in rats seven days after intoxication which corresponds to the occurrence of first motor symptoms. Two-month-old male Wistar rats were unilaterally injected with 6-OHDA to mimic PD pathology and were subsequently divided into two groups to receive either iTBS or sham stimulation for 21 days. The main oxidative parameters were analyzed in the caudoputamen, substantia nigra pars compacta, and serum. iTBS treatment notably mitigated oxidative stress indicators, simultaneously increasing antioxidative parameters in the caudoputamen and substantia nigra pars compacta well after 6-OHDA-induced neurodegeneration process was over. Serum analysis confirmed the systemic effect of iTBS with a decrease in oxidative markers and an increase in antioxidants. Prolonged iTBS exerts a modulatory effect on oxidative/antioxidant parameters in the 6-OHDA-induced PD model, suggesting a potential neuroprotective benefit, even though at this specific time point 6-OHDA-induced oxidative status was unaltered. These results emphasize the need to further explore the mechanisms of iTBS and argue in favor of considering it as a therapeutic intervention in PD and related neurodegenerative diseases.